2004
DOI: 10.1128/cdli.11.4.686-690.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterial Species Differentially Affect Expression of Cell Surface Markers and Cytokines of Dendritic Cells Harvested from Cord Blood

Abstract: The gut microbiota may be important in the postnatal development of the immune system and hence may influence the prevalence of atopic diseases. Bifidobacteria are the most numerous bacteria in the guts of infants, and the presence or absence of certain species could be important in determining the geographic incidence of atopic diseases. We compared the fecal populations of bifidobacteria from children aged 25 to 35 days in Ghana (which has a low prevalence of atopy), New Zealand, and the United Kingdom (high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
111
4
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 24 publications
6
111
4
5
Order By: Relevance
“…27,29,30 Consistent with these studies, recent investigations have stressed the importance of Bifidobacteria species and strains in the modulation of immune reactivity at the intestinal mucosa level. 31 In particular, Bifidobacterium adolescentis has recently received attention because this bacterium is more prevalent in patients with allergic disorders compared to non-allergic subjects, thus indicating that it might be connected to the development of immune dysfunction. 32,33 Based on available experimental and clinical results, it has been proposed that the pathogenesis of T1D is closely linked to events that take place in the intestinal mucosa, where complex interplay between the intestinal microbiota, gut permeability and mucosal immunity determines autoimmune damage to pancreatic beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…27,29,30 Consistent with these studies, recent investigations have stressed the importance of Bifidobacteria species and strains in the modulation of immune reactivity at the intestinal mucosa level. 31 In particular, Bifidobacterium adolescentis has recently received attention because this bacterium is more prevalent in patients with allergic disorders compared to non-allergic subjects, thus indicating that it might be connected to the development of immune dysfunction. 32,33 Based on available experimental and clinical results, it has been proposed that the pathogenesis of T1D is closely linked to events that take place in the intestinal mucosa, where complex interplay between the intestinal microbiota, gut permeability and mucosal immunity determines autoimmune damage to pancreatic beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…Most Bifi dobacterium strains stimulate the production of high levels of IL-10, but only modest levels of IL-12 and TNF-α, and this is also the pattern seen with Gram-negative bacteria of the intestinal microfl ora. [28][29][30] The results of coincubation experiments indicate that there are considerable interactions between bacterial strains that can result in the inhibition or enhancement of DC maturation and IL-12 and IL-10 induction, depending on the combination. 30,31 Similar fi ndings have been reported in LAB-stimulated peripheral blood mononuclear cells (PBMCs).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in vitro, bifidobacterial species differentially affected expression of cell surface markers and cytokine production by dendritic cells harvested from cord blood. B. bifidum, B. longum, and B. pseudocatenulatum, species commonly detected in children in New Zealand and the United Kingdom increased the expression of the dendritic-cell activation marker CD83 and induce IL-10 production, whereas B. infantis, a species commonly isolated in Ghana, does not (Young et al, 2004). By contrast, heat-inactivated B. longum subsp longum and B. adolescentis, known as adult-type bifidobacteria, were significantly stronger inducers of pro-inflammatory cytokine (IL-12 and TNF-alpha) production by a murine macrophage cell line than B. bifidum, B. breve, and B. longum subsp infantis usually isolated from infants (He et al, 2002).…”
Section: Does Dysbiosis Precede Allergic Symptoms? Prospective Studiesmentioning
confidence: 99%
“…Differences in patterns of colonization by bifidobacteria species have also been observed but no clear consensus exists. Young et al (2004) compared the populations of bifidobacteria in feces from children aged 25 to 35 days in Ghana (which has a low prevalence of atopy), New Zealand, and the United Kingdom (high-prevalence countries): almost all fecal samples from Ghana contained Bifidobacterium longum subsp infantis whereas those from the children living in the other countries did not. The authors suggested that place of birth influences the patterns of bifidobacterial species present.…”
Section: Does Dysbiosis Precede Allergic Symptoms? Prospective Studiesmentioning
confidence: 99%